Tubular nanofiber membrane material as well as preparation method and application thereof

The tubular nanofiber membrane materials prepared by bionic modified two-dimensional braided tube substrate and electrospinning technology, combined with PMIA and MnO2 nanoparticles, solve the problem of low efficiency in formaldehyde removal by existing air filter materials, achieve high-efficiency filtration and significant formaldehyde removal, reducing production costs and secondary pollution risks.

CN119773345AActive Publication Date: 2025-04-08HEBEI UNIV OF SCI & TECH
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202510039254.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-08
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

Existing air filter materials are inefficient in removing formaldehyde from indoor air, and have a long purification cycle and secondary pollution risk, making it difficult to use effectively in air filters.

Method used

Using a bionic modified two-dimensional braided tube substrate, tubular nanofiber membrane materials are prepared through electrospinning technology, combining polyisophthalamide (PMIA) and MnO2 nanoparticles with excellent high temperature resistance to form an efficient air filtering material.

Benefits of technology

It realizes efficient filtration of PM2.5 and significantly remove formaldehyde, reducing production costs, improving preparation efficiency and service life, and avoiding the risk of secondary pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119773345A_ABST
    Figure CN119773345A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of air filtering materials, and particularly discloses a tubular nanofiber membrane material as well as a preparation method and application thereof. The preparation method comprises the following steps: firstly, carrying out surface modification on a two-dimensional braided tube in a surface modification liquid, and then carrying out bionic modification in a manganese-containing bionic modification liquid to obtain a bionic modified two-dimensional braided tube substrate; and performing electrostatic spinning on the mixed spinning solution by taking the tubular nanofiber membrane as a receiving substrate to obtain the tubular nanofiber membrane material. The mixed spinning solution is obtained by mixing a polyisophthaloyl metaphenylene diamine spinning solution or a polyisophthaloyl metaphenylene diamine / MnO2 spinning solution with a polyvinylidene fluoride-hexafluoropropylene copolymer spinning solution. The obtained tubular nanofiber membrane material is high in filling density and does not need to be supported by a framework; a tubular air filter prepared from the composite material is good in mechanical property, filtering property, formaldehyde removal property and durability and excellent in antibacterial property and has universality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of air filter materials, and in particular to a tubular nanofiber membrane material and a preparation method and application thereof. Background Art

[0002] With the rapid development of industry, air pollution is becoming increasingly serious. Long-term exposure to polluted environments can cause various diseases. Air filters used in combination with high-efficiency air filter materials have become one of the most effective ways to remove solid particulate matter (PM) from the air, and the structure and performance of the filter element have become key factors affecting air filters. Compared with flat filter substrates, tubular nanofiber membrane materials have the advantages of good self-supporting performance and high packing density, which is conducive to simplifying the structure of air filters and improving preparation efficiency.

[0003] In addition to solid particulate matter, formaldehyde is identified as a first-level carcinogen. Long-term exposure to an environment with excessive formaldehyde can lead to chronic poisoning, causing respiratory and digestive tract diseases, etc., greatly increasing the probability of developing leukemia, tumors and cancer, and in more serious cases causing death.

[0004] The removal of HCHO from indoor air is mainly achieved by using air purifiers with absorption media or by increasing the air exchange rate through air conditioning systems. However, the range of purifiers currently available is limited to those based on traditional activated carbon adsorption materials, which require long cycles and pose a risk of secondary contamination.

[0005] With the development of catalysts, catalytic oxidation has become a research hotspot for formaldehyde removal. Among the transition metal oxide catalysts used, manganese dioxide (MnO2) is widely used for HCHO catalytic removal, which can convert HCHO into CO2 and H2O. However, MnO2 particle catalysts are difficult to use in air filters and are not suitable for the removal of HCHO in room temperature air in practical applications.

[0006] Therefore, how to provide a tubular nanofiber membrane material with good mechanical properties, filtration properties, formaldehyde removal properties and durability, and then prepare a tubular nanofiber air filter with excellent antibacterial properties and universal applicability is a difficult problem that needs to be solved urgently in this field. Summary of the invention

[0007] In view of this, the present invention provides a tubular nanofiber membrane material and a preparation method and application thereof, which solve the problems of poor supporting performance and low packing density of existing planar filter substrates; and also solve the problems of long purification cycle and secondary pollution risk of existing purifiers for HCHO in the air.

[0008] In order to achieve the above object, the present invention adopts the following technical solution:

[0009] A method for preparing a tubular nanofiber membrane material comprises the following steps:

[0010] 1) immersing the two-dimensional braided tube in a surface modification liquid to perform surface modification to obtain a surface-modified two-dimensional braided tube;

[0011] 2) The surface-modified two-dimensional braided tube is immersed in a manganese-containing bionic modification liquid to perform bionic modification, and MnO2 is grown in situ to obtain a bionic modified two-dimensional braided tube substrate;

[0012] 3) using the bionic modified two-dimensional braided tube substrate as a receiving substrate, electrospinning the mixed spinning solution to obtain a tubular nanofiber membrane material;

[0013] The mixed spinning solution is obtained by mixing poly(m-phenylene isophthalamide) spinning solution or poly(m-phenylene isophthalamide) / MnO2 spinning solution with poly(vinylidene fluoride)-hexafluoropropylene copolymer spinning solution.

[0014] Preferably, the two-dimensional braided tube in step 1) comprises a two-dimensional braided tube of polyethylene terephthalate fiber, a two-dimensional braided tube of polyacrylonitrile fiber, a two-dimensional braided tube of polyamide fiber, or a two-dimensional braided tube of polyolefin fiber.

[0015] Preferably, the surface modification liquid comprises one or more of a dopamine hydrochloride aqueous solution, a tannic acid aqueous solution and a catechol aqueous solution;

[0016] The mass concentration of the surface modification liquid is 0.1-10 g / L.

[0017] Preferably, the pH value of the surface modification is 7 to 10, and the surface modification time is 6 to 48 hours.

[0018] Preferably, the manganese-containing biomimetic modification liquid in step 2) is a potassium permanganate solution; the molar concentration of the manganese-containing biomimetic modification liquid is 0.01-0.4 mol / L.

[0019] Preferably, the time of the bionic modification in step 2) is 3 to 24 hours, and the temperature of the bionic modification is 20 to 80°C.

[0020] Preferably, the volume ratio of the poly(m-phenylene isophthalamide) spinning solution or the poly(m-phenylene isophthalamide) / MnO2 spinning solution to the poly(vinylidene fluoride)-hexafluoropropylene copolymer spinning solution in the mixed spinning solution in step 3) is 3 to 10:1.

[0021] Preferably, the electrospinning spinning voltage has a positive high voltage of 10 to 25 kV, a negative high voltage of -1 to -5 kV, a distance between the spinning needle and the receiving substrate is 5 to 20 cm, and a feeding speed of 0.1 to 2 mL / h.

[0022] Another object of the present invention is to provide a tubular nanofiber membrane material prepared by the above preparation method.

[0023] Another object of the present invention is to provide a tubular nanofiber membrane material for use as an air filter element.

[0024] It can be seen from the above technical solutions that, compared with the prior art, the present invention has the following beneficial effects:

[0025] The present invention uses a biomimetic modified two-dimensional braided tube substrate as a receiving matrix, polyisophthalamide (PMIA) with excellent high temperature resistance as one of the main film-making materials of the nanofiber membrane, and adopts electrostatic spinning technology to prepare PMIA nanofiber air filter material with high efficiency filtration performance. Different from the planar structure of traditional nanofiber air filter materials, the nanofiber air filter material prepared by the present invention has a unique tubular structure, which can improve its air filtration performance and at the same time, give the PMIA nanofiber air filter material multifunctionality. The unique filter structure design reduces production costs, improves preparation efficiency and service life, and provides a more comprehensive reference for practical applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0027] Figure 1 This is a surface morphology diagram of the modified PET two-dimensional braided tube material in Example 1 of the present invention;

[0028] Figure 2 This is a cross-sectional SEM image of the tubular nanofiber membrane material prepared in Example 1 of the present invention;

[0029] Figure 3 This is a SEM image of the tubular nanofiber membrane material prepared in Comparative Example 1 of the present invention;

[0030] Figure 4 This is the SEM image of the tubular nanofiber membrane material prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0031] The present invention provides a method for preparing a tubular nanofiber membrane material, comprising the following steps:

[0032] 1) immersing the two-dimensional braided tube in a surface modification liquid to perform surface modification to obtain a surface-modified two-dimensional braided tube;

[0033] 2) The surface-modified two-dimensional braided tube is immersed in a manganese-containing bionic modification liquid to perform bionic modification, and MnO2 is grown in situ to obtain a bionic modified two-dimensional braided tube substrate;

[0034] 3) Using the bionic modified two-dimensional braided tube substrate as a receiving substrate, the mixed spinning solution is electrospun to obtain a tubular nanofiber membrane material.

[0035] In the present invention, the mixed spinning solution is obtained by mixing poly(meta-phenylene isophthalamide) spinning solution or poly(meta-phenylene isophthalamide) / MnO2 spinning solution with poly(vinylidene fluoride)-hexafluoropropylene copolymer spinning solution; the mixing temperature is preferably 60-80°C, specifically 62°C, 64°C, 65°C, 66°C, 68°C, 70°C, 72°C, 75°C, and 78°C.

[0036] In the present invention, the two-dimensional braided tube in step 1) includes a two-dimensional braided tube of polyethylene terephthalate fiber, a two-dimensional braided tube of polyacrylonitrile fiber, a two-dimensional braided tube of polyamide fiber, and a two-dimensional braided tube of polyolefin fiber.

[0037] In the present invention, the surface modification liquid includes one or more of a dopamine hydrochloride aqueous solution, a tannic acid aqueous solution and a catechol aqueous solution;

[0038] In the present invention, the mass concentration of the surface modification liquid is 0.1-10 g / L, specifically 0.5 g / L, 1 g / L, 2 g / L, 3 g / L, 4 g / L, 5 g / L, 6 g / L, 7 g / L, 8 g / L, and 9 g / L.

[0039] In the present invention, the pH value of the surface modification is 7 to 10, specifically 7.5, 8, 8.5, 9, 9.5; the time of surface modification is 6 to 48 hours, specifically 8 hours, 10 hours, 12 hours, 18 hours, 24 hours, 30 hours, 36 hours.

[0040] In the present invention, the manganese-containing bionic modified liquid in step 2) is a potassium permanganate solution; the molar concentration of the manganese-containing bionic modified liquid is 0.01-0.4 mol / L, specifically 0.05 mol / L, 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, 0.25 mol / L, 0.3 mol / L, 0.35 mol / L.

[0041] In the present invention, the time of the bionic modification in step 2) is 3 to 24 hours, specifically 4 hours, 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, and 22 hours; the temperature of the bionic modification is 20 to 80°C, specifically 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, and 75°C.

[0042] In the present invention, the volume ratio of the poly(m-phenylene isophthalamide) spinning solution or the poly(m-phenylene isophthalamide) / MnO2 spinning solution to the poly(vinylidene fluoride)-hexafluoropropylene copolymer spinning solution in the mixed spinning solution in step 3) is 3 to 10:1, preferably 5 to 7:1, and more preferably 6:1.

[0043] In the present invention, the solvent of the poly(m-phenylene isophthalamide) spinning solution, the poly(m-phenylene isophthalamide) / MnO2 spinning solution, and the poly(vinylidene fluoride)-hexafluoropropylene copolymer spinning solution includes one or more of N,N-dimethylacetamide, N,N-dimethylformamide and N-methylpyrrolidone.

[0044] In the present invention, the preparation method of poly(meta-phenylene isophthalamide) spinning solution is: LiCl and poly(meta-phenylene isophthalamide) are added to a solvent in sequence to obtain a poly(meta-phenylene isophthalamide) spinning solution; the mass concentration of the poly(meta-phenylene isophthalamide) spinning solution is 5 to 25wt.%, and can be specifically 8wt.%, 10wt.%, 12wt.%, 15wt.%, 18wt.%, 20wt.%, 22wt.%, or 24wt.%.

[0045] In the present invention, the mass concentration of the polyvinylidene fluoride-hexafluoropropylene copolymer spinning solution is 5-30wt.%, specifically 8wt.%, 10wt.%, 12wt.%, 15wt.%, 18wt.%, 20wt.%, 22wt.%, 24wt.%, 25wt.%, 28wt.%.

[0046] In the present invention, the preparation method of poly(meta-phenylene isophthalamide) / MnO2 spinning solution is: LiCl, MnO2 powder and poly(meta-phenylene isophthalamide) are added to a solvent in sequence to obtain the poly(meta-phenylene isophthalamide) / MnO2 spinning solution.

[0047] In the present invention, the dosage ratio of LiCl, MnO2 powder, poly(m-phenylene isophthalamide) and solvent is 1-5:0-8:5-25:62-94, preferably 2-4:1-6:8-20:65-90, further preferably 3:2-5:10-18:70-80, and further preferably 3:4:15:75; the addition amount of MnO2 powder is not 0.

[0048] In the present invention, the positive high voltage spinning voltage of the electrospinning is 10 to 25 kV, specifically 12 kV, 15 kV, 18 kV, 20 kV, 22 kV, and 24 kV; the negative high voltage is -1 to -5 kV, specifically -2 kV, -3 kV, and -4 kV; the distance between the spinning needle and the receiving substrate is 5 to 20 cm, specifically 6 cm, 8 cm, 10 cm, 12 cm, 15 cm, and 18 cm; the feeding speed is 0.1 to 2 mL / h, 0.2 mL / h, 0.5 mL / h, 0.8 mL / h, 1 mL / h, 1.2 mL / h, 1.5 mL / h, and 1.8 mL / h.

[0049] The present invention also provides a tubular nanofiber membrane material prepared by the above preparation method.

[0050] The invention also provides an application of the tubular nanofiber membrane material as an air filter element.

[0051] In the present invention, the preparation method of the air filter element is as follows: using the tubular nanofiber membrane material as the filter material, using epoxy resin to encapsulate one end of the tubular nanofiber membrane material in a nylon tube, and then inserting it into a silicone base in a honeycomb arrangement to make an air filter element.

[0052] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0053] The PET two-dimensional braided tubes used in all embodiments of the present invention were purchased from Xuzhou Shiheng Environmental Protection Technology Co., Ltd. (inner diameter 1.1 cm, outer diameter 1.8 cm), but this is not considered to be a limitation of the present invention.

[0054] Example 1

[0055] (1) Surface biomimetic modification of braided tube: The PET two-dimensional braided tube was immersed in a dopamine hydrochloride solution (mass concentration of 2 g / L), and the pH value of the solution was adjusted to 8.5. After reacting at room temperature for 24 hours, it was placed in a 0.03 mol / L potassium permanganate solution and soaked at 60°C for 5 hours. Take it out and rinse it thoroughly with deionized water and dry it; the surface morphology of the modified PET two-dimensional braided tube material is as follows Figure 1 As shown, through Figure 1 It can be seen that MnO2 nanoparticles were successfully grown in situ on the fiber surface.

[0056] (2) Preparation of spinning solution: 1 g of LiCl powder was weighed into a three-necked round-bottom flask containing 43 g of dimethylacetamide solvent, and ultrasonicated for 30 min, and then mechanically stirred in a 65°C water bath for 1 h to uniformly disperse the above powder. Then 6 g of poly(m-phenylene isophthalamide) was added to the above solution and stirred for 5 h until the poly(m-phenylene isophthalamide) was completely dissolved to form a uniform poly(m-phenylene isophthalamide) spinning solution (PMIA spinning solution).

[0057] A certain amount of 9 g of polyvinylidene fluoride-hexafluoropropylene copolymer was added to 41 g of dimethylacetamide solution, and then stirred in a water bath at 65° C. for 5 hours and degassed to obtain a polyvinylidene fluoride-hexafluoropropylene copolymer spinning solution (PVDF-HFP spinning solution).

[0058] The PMIA spinning solution and the PVDF-HFP spinning solution were mixed at a ratio of 8:1 to obtain a mixed spinning solution.

[0059] (3) The mixed spinning solution was added into a syringe, and the modified braided tube was used as the receiving substrate. The positive voltage for spinning was 15 kV. The receiving negative voltage was -2 kV, the spinning distance was 10 cm, and the feeding speed was 0.2 mL / h. The electrospinning equipment was used for spinning to obtain a tubular PMIA / MnO2 nanofiber membrane material. The cross-sectional SEM image of the tubular PMIA / MnO2 nanofiber membrane material is shown in FIG. Figure 2 As shown, through Figure 2 It can be seen that the nanofiber layer is tightly wrapped on the outer surface of the braided tube.

[0060] After testing, the obtained tubular nanofiber air filter has a PM2.5 filtration efficiency of 97.1% and a formaldehyde removal efficiency of more than 73.7%.

[0061] Comparative Example 1

[0062] (1) Preparation of spinning solution: 1 g of LiCl powder was weighed into a three-necked round-bottom flask containing 43 g of dimethylacetamide solvent, and ultrasonicated for 30 min, and then mechanically stirred in a 65°C water bath for 1 h to uniformly disperse the powder. Then 6 g of poly(m-phenylene isophthalamide) was added to the solution and stirred for 5 h until the poly(m-phenylene isophthalamide) was completely dissolved to form a uniform poly(m-phenylene isophthalamide) spinning solution (PMIA spinning solution).

[0063] A certain amount of 9 g of polyvinylidene fluoride-hexafluoropropylene copolymer was added to 41 g of dimethylacetamide solution, and then stirred in a water bath at 65° C. for 5 hours and degassed to obtain a polyvinylidene fluoride-hexafluoropropylene copolymer spinning solution (PVDF-HFP spinning solution).

[0064] The PMIA spinning solution and the PVDF-HFP spinning solution were mixed at a ratio of 8:1 to obtain a mixed spinning solution.

[0065] (2) The mixed spinning solution was added into a syringe, and an unmodified PET two-dimensional braided tube was used as a receiving substrate. The positive voltage for spinning was 15 kV, the negative voltage for receiving was -2 kV, the spinning distance was 10 cm, and the feeding speed was 0.2 mL / h. Electrospinning equipment was used for spinning to obtain a tubular PMIA nanofiber membrane material. Its SEM morphology is shown in FIG. Figure 3 As shown, through Figure 3 It can be seen that the nanofiber structure is relatively uniform and the fiber surface is relatively smooth.

[0066] After testing, the obtained tubular nanofiber air filter has a PM2.5 filtration efficiency of 96.9% and has no formaldehyde degradation performance because the tubular nanofiber membrane material does not contain functional substances that can degrade formaldehyde.

[0067] Comparative Example 2

[0068] (1) Surface biomimetic modification of braided tube: The PET two-dimensional braided tube was immersed in a dopamine hydrochloride solution (mass concentration of 2 g / L), and the pH value of the solution was adjusted to 8.5. After reacting at room temperature for 24 h, it was placed in a 0.03 mol / L potassium permanganate solution and immersed at 60°C for 5 h. It was taken out and rinsed thoroughly with deionized water and dried.

[0069] (2) Preparation of spinning solution: 1 g of LiCl powder was weighed into a three-necked round-bottom flask containing 43 g of dimethylacetamide solvent, and ultrasonicated for 30 min, and then mechanically stirred in a 65°C water bath for 1 h to uniformly disperse the above powder. Then 6 g of poly(m-phenylene isophthalamide) was added to the above solution and stirred for 5 h until the poly(m-phenylene isophthalamide) was completely dissolved to form a uniform poly(m-phenylene isophthalamide) spinning solution (PMIA spinning solution), thereby obtaining an electrospinning stock solution.

[0070] (3) The spinning solution is added into a syringe, and the modified braided tube is used as a receiving substrate. The positive voltage for spinning is 15 kV. The receiving negative voltage is -2 kV, the spinning distance is 10 cm, and the feeding speed is 0.2 mL / h. The spinning is performed using an electrospinning device to obtain a tubular PMIA nanofiber membrane material.

[0071] The test results show that the obtained tubular nanofiber air filter has a PM2.5 filtration efficiency of 95.1% and a formaldehyde removal efficiency of more than 71.5%. Adding PVDF-HFP to the spinning solution is beneficial to the formation of nanofibers during the electrospinning process.

[0072] Example 2

[0073] (1) Surface biomimetic modification of braided tube: The PET two-dimensional braided tube was immersed in a dopamine hydrochloride solution (mass concentration of 4 g / L), and the pH value of the solution was adjusted to 8.5. After reacting at room temperature for 24 h, it was placed in a 0.11 mol / L potassium permanganate solution and soaked at 60 °C for 5 h. Take it out and rinse it thoroughly with deionized water and dry it.

[0074] (2) Preparation of spinning solution: 1 g of LiCl powder was weighed into a three-necked round-bottom flask containing 43 g of dimethylacetamide solvent, and ultrasonicated for 30 min, and then mechanically stirred in a 65°C water bath for 1 h to uniformly disperse the powder. 0.5 g of MnO2 powder was added to the above solution and stirred for 1 h, and then 6 g of poly(m-phenylene isophthalamide) was added to the above solution and stirred for 5 h, until the poly(m-phenylene isophthalamide) was completely dissolved to form a uniform poly(m-phenylene isophthalamide) spinning solution (PMIA / MnO2 spinning solution).

[0075] A certain amount of 9g of polyvinylidene fluoride-hexafluoropropylene copolymer was added to 41g of dimethylacetamide solution, and then stirred in a water bath at 65°C for 5h, and then degassed to obtain a polyvinylidene fluoride-hexafluoropropylene copolymer spinning solution (PVDF-HFP spinning solution).

[0076] The PMIA / MnO2 spinning solution and the PVDF-HFP solution were mixed at a ratio of 4:1 to obtain a mixed spinning solution.

[0077] (3) The spinning solution was added into a syringe, and the modified braided tube was used as a receiving substrate. The positive voltage of spinning was 15 kV, and the negative voltage of the receiving end was -2 kV. The spinning distance was 10 cm, and the feeding speed was 0.3 mL / h. The electrospinning equipment was used for spinning to obtain a tubular PMIA / MnO2 nanofiber membrane material, and its SEM morphology was as follows: Figure 4 As shown, through Figure 4 It can be seen that there are a large number of MnO2 nanoparticles on the surface of the nanofibers.

[0078] After testing, the obtained tubular nanofiber air filter has a PM2.5 filtration efficiency of 97.4% and a formaldehyde removal efficiency of more than 97.2%.

[0079] Example 3

[0080] (1) Surface biomimetic modification of braided tube: The PET two-dimensional braided tube was immersed in a dopamine hydrochloride solution (mass concentration of 6 g / L), and the pH value of the solution was adjusted to 8.5. After reacting at room temperature for 24 h, it was placed in a 0.11 mol / L potassium permanganate solution and soaked at 60°C for 5 h. It was taken out and rinsed thoroughly with deionized water and dried.

[0081] (2) Preparation of spinning solution: 1 g of LiCl powder was weighed into a three-necked round-bottom flask containing 42.25 g of dimethylacetamide solvent, and ultrasonicated for 30 min, and then mechanically stirred in a 65°C water bath for 1 h to uniformly disperse the powder. 1 g of MnO2 powder was added to the above solution and stirred continuously for 1 h, and then 6 g of poly(m-phenylene isophthalamide) was added to the above solution and stirred continuously for 5 h, until the poly(m-phenylene isophthalamide) was completely dissolved to form a uniform poly(m-phenylene isophthalamide) spinning solution (PMIA / MnO2 spinning solution).

[0082] A certain amount of 9g of polyvinylidene fluoride-hexafluoropropylene copolymer was added to 41g of dimethylacetamide solution, and then stirred in a water bath at 65°C for 5h, and then degassed to obtain a polyvinylidene fluoride-hexafluoropropylene copolymer spinning solution (PVDF-HFP spinning solution).

[0083] The PMIA / MnO2 spinning solution and the PVDF-HFP solution were mixed at a ratio of 6:1 to obtain a mixed spinning solution.

[0084] (3) The spinning solution is added into a syringe, and the modified braided tube is used as a receiving substrate. The positive voltage of spinning is 15 kV. The receiving negative voltage is -2 kV, and the feeding speed is 0.4 mL / h. The spinning distance is 10 cm. The spinning is carried out using an electrospinning device to obtain a tubular PMIA / MnO2 nanofiber membrane material.

[0085] After testing, the obtained tubular nanofiber air filter has a PM2.5 filtration efficiency of 96.5% and a formaldehyde removal efficiency of more than 99.9%.

[0086] Example 4

[0087] (1) Surface biomimetic modification of braided tube: The polyamide two-dimensional braided tube was immersed in a tannic acid aqueous solution (mass concentration of 8 g / L), and the pH value of the solution was adjusted to 9. After reacting at room temperature for 48 h, it was placed in a 0.3 mol / L potassium permanganate solution and soaked at 70°C for 5 h. It was taken out and thoroughly rinsed with deionized water and dried.

[0088] (2) Preparation of spinning solution: 1.5 g of LiCl powder was weighed into a three-necked round-bottom flask containing 40.5 g of dimethylacetamide solvent, and ultrasonicated for 30 min, and then mechanically stirred in a 65°C water bath for 1 h to uniformly disperse the powder. 1.5 g of MnO2 powder was added to the above solution and stirred continuously for 1 h, and then 8 g of poly(m-phenylene isophthalamide) was added to the above solution and stirred continuously for 5 h, until the poly(m-phenylene isophthalamide) was completely dissolved, forming a uniform poly(m-phenylene isophthalamide) spinning solution (PMIA / MnO2 spinning solution).

[0089] A certain amount of 10g of polyvinylidene fluoride-hexafluoropropylene copolymer was added to 40g of dimethylacetamide solution, and then stirred in a water bath at 65°C for 5h, and then degassed to obtain a polyvinylidene fluoride-hexafluoropropylene copolymer spinning solution (PVDF-HFP spinning solution).

[0090] The PMIA / MnO2 spinning solution and the PVDF-HFP solution were mixed at a ratio of 10:1 to obtain a mixed spinning solution.

[0091] (3) The spinning solution is added into a syringe, and the modified braided tube is used as a receiving substrate. The positive voltage of spinning is 20 kV. The receiving negative voltage is -3 kV, and the feeding speed is 0.3 mL / h. The spinning distance is 15 cm. The spinning is carried out using an electrospinning device to obtain a tubular PMIA / MnO2 nanofiber membrane material.

[0092] After testing, the obtained tubular nanofiber air filter has a PM2.5 filtration efficiency of 97.8% and a formaldehyde removal efficiency of more than 99.8%.

[0093] Example 5

[0094] (1) Surface biomimetic modification of braided tube: The polyacrylonitrile two-dimensional braided tube was immersed in a catechol aqueous solution (mass concentration of 10 g / L), and the pH value of the solution was adjusted to 9.5. After reacting at room temperature for 6 h, it was placed in a 0.01 mol / L potassium permanganate solution and soaked at 80°C for 5 h. It was taken out and rinsed thoroughly with deionized water and dried.

[0095] (2) Preparation of spinning solution: 2 g of LiCl powder was weighed into a three-necked round-bottom flask containing 37 g of dimethylacetamide solvent, and ultrasonicated for 30 min, and then mechanically stirred in a 65°C water bath for 1 h to uniformly disperse the powder. 1.0 g of MnO2 powder was added to the above solution and stirred continuously for 1 h, and then 10 g of poly(m-phenylene isophthalamide) was added to the above solution and stirred continuously for 5 h, until the poly(m-phenylene isophthalamide) was completely dissolved to form a uniform poly(m-phenylene isophthalamide) spinning solution (PMIA / MnO2 spinning solution).

[0096] A certain amount of 12g of polyvinylidene fluoride-hexafluoropropylene copolymer was added to 38g of dimethylacetamide solution, and then stirred in a water bath at 65°C for 5h, and then degassed to obtain a polyvinylidene fluoride-hexafluoropropylene copolymer spinning solution (PVDF-HFP spinning solution).

[0097] The PMIA / MnO2 spinning solution and the PVDF-HFP solution were mixed at a ratio of 3:1 to obtain a mixed spinning solution.

[0098] (3) The spinning solution is added into a syringe, and the modified braided tube is used as a receiving substrate. The positive voltage of spinning is 12 kV. The receiving negative voltage is -1 kV, and the feeding speed is 1.2 mL / h. The spinning distance is 18 cm. The electrospinning equipment is used for spinning to obtain a tubular PMIA / MnO2 nanofiber membrane material.

[0099] After testing, the obtained tubular nanofiber air filter has a PM2.5 filtration efficiency of 95.8% and a formaldehyde removal efficiency of more than 93.8%.

[0100] Example 6

[0101] (1) Surface biomimetic modification of braided tube: The polyacrylonitrile two-dimensional braided tube was immersed in a tannic acid aqueous solution (mass concentration of 2 g / L), and the pH value of the solution was adjusted to 7.5. After reacting at room temperature for 12 h, it was placed in a 0.4 mol / L potassium permanganate solution and soaked at 50°C for 6 h. It was taken out and rinsed thoroughly with deionized water and dried.

[0102] (2) Preparation of spinning solution: 1 g of LiCl powder was weighed into a three-necked round-bottom flask containing 40 g of dimethylacetamide solvent, and ultrasonicated for 30 min, and then mechanically stirred in a 65°C water bath for 1 h to uniformly disperse the powder. 1.0 g of MnO2 powder was added to the above solution and stirred continuously for 1 h, and then 9 g of poly(m-phenylene isophthalamide) was added to the above solution and stirred continuously for 5 h, until the poly(m-phenylene isophthalamide) was completely dissolved to form a uniform poly(m-phenylene isophthalamide) spinning solution (PMIA / MnO2 spinning solution).

[0103] A certain amount of 10g of polyvinylidene fluoride-hexafluoropropylene copolymer was added to 40g of dimethylacetamide solution, and then stirred in a water bath at 65°C for 5h, and then degassed to obtain a polyvinylidene fluoride-hexafluoropropylene copolymer spinning solution (PVDF-HFP spinning solution).

[0104] The PMIA / MnO2 spinning solution and the PVDF-HFP solution were mixed at a ratio of 8:1 to obtain a mixed spinning solution.

[0105] (3) The spinning solution is added into a syringe, and the modified braided tube is used as a receiving substrate. The positive voltage of spinning is 15 kV. The receiving negative voltage is -1 kV, and the feeding speed is 0.3 mL / h. The spinning distance is 15 cm. The electrospinning equipment is used for spinning to obtain a tubular PMIA / MnO2 nanofiber membrane material.

[0106] After testing, the obtained tubular nanofiber air filter has a PM2.5 filtration efficiency of 96.3% and a formaldehyde removal efficiency of more than 95.8%.

[0107] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0108] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a tubular nanofiber membrane material, characterized in that: The steps include: 1) immersing the two-dimensional braided tube in a surface modification liquid to perform surface modification to obtain a surface-modified two-dimensional braided tube; 2) The surface-modified two-dimensional braided tube is immersed in a manganese-containing bionic modification liquid to perform bionic modification, and MnO2 is grown in situ to obtain a bionic modified two-dimensional braided tube substrate; 3) using the bionic modified two-dimensional braided tube substrate as a receiving substrate, electrospinning the mixed spinning solution to obtain a tubular nanofiber membrane material; The mixed spinning solution is obtained by mixing poly(m-phenylene isophthalamide) spinning solution or poly(m-phenylene isophthalamide) / MnO2 spinning solution with poly(vinylidene fluoride)-hexafluoropropylene copolymer spinning solution.

2. The method for preparing a tubular nanofiber membrane material according to claim 1, characterized in that: The two-dimensional braided tube in step 1) includes a two-dimensional braided tube of polyethylene terephthalate fiber, a two-dimensional braided tube of polyacrylonitrile fiber, a two-dimensional braided tube of polyamide fiber, and a two-dimensional braided tube of polyolefin fiber.

3. The method for preparing a tubular nanofiber membrane material according to claim 1 or 2, characterized in that: The surface modification liquid includes one or more of a dopamine hydrochloride aqueous solution, a tannic acid aqueous solution and a catechol aqueous solution; The mass concentration of the surface modification liquid is 0.1-10 g / L.

4. The method for preparing a tubular nanofiber membrane material according to claim 3, characterized in that: The pH value of the surface modification is 7 to 10, and the surface modification time is 6 to 48 hours.

5. The method for preparing a tubular nanofiber membrane material according to claim 4, characterized in that: The manganese-containing bionic modification liquid in step 2) is a potassium permanganate solution; the molar concentration of the manganese-containing bionic modification liquid is 0.01-0.4 mol / L.

6. The method for preparing a tubular nanofiber membrane material according to claim 5, characterized in that: The time of the bionic modification in step 2) is 3 to 24 hours, and the temperature of the bionic modification is 20 to 80°C.

7. A method for preparing a tubular nanofiber membrane material according to any one of claims 4 to 6, characterized in that: The volume ratio of the poly(m-phenylene isophthalamide) spinning solution or the poly(m-phenylene isophthalamide) / MnO2 spinning solution to the poly(vinylidene fluoride)-hexafluoropropylene copolymer spinning solution in the mixed spinning solution in step 3) is 3 to 10:

1.

8. The method for preparing a tubular nanofiber membrane material according to claim 7, characterized in that: The electrospinning has a positive high voltage of 10 to 25 kV, a negative high voltage of -1 to -5 kV, a distance between the spinning needle and the receiving substrate of 5 to 20 cm, and a feeding speed of 0.1 to 2 mL / h.

9. The tubular nanofiber membrane material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the tubular nanofiber membrane material according to claim 9 as an air filter element.

Citation Information

Patent Citations

  • A tubular braid and composite hollow fiber membrane using the same

    CN101588859A

  • Electrostatic spinning preparation method of manganese dioxide / polyacrylonitrile (MD / PAN) base oxygenolysis methanal type nanofiber membrane

    CN103382623A

  • Method for preparing electrode materials with hollow carbon fibers coated with manganese dioxide

    CN105513822A

  • Preparation method of conductive polyimide fiber material

    CN106283659A

  • Fiber tube reinforced hollow fiber composite biofilm as well as preparation method and application thereof

    CN110180403A